Connectivism: Developing Superior Human Resources with Entrepreneurial Character in the Financial and Banking Sector - Kusnanto, Danang Kusnanto; Syahlan , Fatra; Jalaludin, Engga; Budiwati , Neti (Universitas Ibn Khladun Bogor, 2024)
The rapid advancements in digital innovation pose significant challenges for human resources practitioners in the financial and banking sectors. Connectivism, a learning theory that emphasizes networks and technology, provides a framework for developing entrepreneurial characteristics in human resources. The demand for adaptive, innovative, and entrepreneurial human resources capabilities is increasingly urgent to navigate the dynamic and competitive business environment. This study aims to assess the impact of connectivism on human resources performance, identify effective implementation strategies, and evaluate the enhancement of organizational competitiveness. The research employs a comprehensive literature review methodology, utilizing qualitative analysis from various academic sources. Findings indicate that connectivism enhances human resources performance by fostering continuous learning, broader knowledge access, and the development of adaptive skills. Additionally, connectivism promotes entrepreneurial characteristics such as innovation, creativity, and risk-taking. Challenges such as resistance to change and the need for significant investment in technology must be addressed. In conclusion, integrating connectivism into human resources development strategies not only improves individual employee effectiveness but also strengthens the organization's competitive position in the rapidly evolving market. Thus, connectivism offers a relevant and effective approach to addressing the challenges faced by human resources in the financial and banking sectors in the current digital era. By leveraging networked learning and technological integration, organizations can better prepare their workforce to meet the demands of an increasingly interconnected and fast-paced business landscape, ensuring sustained growth and innovation.